2016
DOI: 10.1111/bpa.12385
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the mitochondrial BCAT protein correlates with improved patient survival in IDH‐WT gliomas

Abstract: We recommend you cite the published version. The publisher's URL is: http://dx.doi.org/10.1111/bpa.12385 Refereed: YesThis is the peer reviewed version of the following article: Conway, M. E., Hull, J., El Hindy, M., Taylor, S., El Amraoui, F., Paton?Thomas, C., White, P., Williams, H., Haynes, H., Bertoni, A., Radlwimmer, B., Hutson, S. and Kurian, K. (2016) Decreased expression of the mitochondrial bcat protein correlates with improved patient survival in idh?wt gliomas. Brain Pathology, which has been pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Branched-chain amino acids (BCAA) catabolism is abnormal in many human diseases (Burrage et al, 2014, Sonnet et al, 2016, Watanabe et al, 1984). Branched-chain amino transferase (BCAT) is the first enzyme in BCAA catabolism which has a higher activity in tumors and has been shown to be a useful marker for grading and genetic characterization in glioma, colorectal cancer (CRC) and medulloblastoma (Conway et al, 2016, de Bont et al, 2008, Mitchell et al, 2014). However, healthy human prostate tissue was found to have elevated BCAT levels relative to malignant tissue (Billingsley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Branched-chain amino acids (BCAA) catabolism is abnormal in many human diseases (Burrage et al, 2014, Sonnet et al, 2016, Watanabe et al, 1984). Branched-chain amino transferase (BCAT) is the first enzyme in BCAA catabolism which has a higher activity in tumors and has been shown to be a useful marker for grading and genetic characterization in glioma, colorectal cancer (CRC) and medulloblastoma (Conway et al, 2016, de Bont et al, 2008, Mitchell et al, 2014). However, healthy human prostate tissue was found to have elevated BCAT levels relative to malignant tissue (Billingsley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…25 While this was the first study to use an animal model of BCATm in cancer, other studies using siRNA to silence BCATm, or comparing the expression of BCATm in healthy and cancer tissues, also suggested that a loss of BCATm leads to suppression of tumour growth, while BCATm overexpression has the opposite effect. 23,24,39 In this study, however, the diet composition significantly impacted the ability of BCATmKO mice to repress cancer. As previously reported, BCATmKO mice are maintained on a choice BCAA diet to escape the deleterious effects of toxic BCAA accumulation.…”
Section: Discussionmentioning
confidence: 53%
“…Heart hypertrophy was previously linked with the well-established role of BCAAs, and particularly leucine, in the regulation of mTORC1 signalling. 23,24,39 In fact, feeding BCATmKO mice with a diet supplemented with rapamycin prevented the heart enlargement of BCATmKO animals, suggesting that mTORC1 is the mediator of these effects. 35…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The hBCAT proteins exist in two main isoforms, the mitochondrial hBCAT isoform (hBCATm protein, BCAT2 gene) is widely expressed in most tissues, whereas the cytosolic hBCAT (hBCATc protein, BCAT1 gene) is restricted to highly specialised tissues including brain and placenta [16]. Increased levels of the BCAT gene, BCAT1 have been extensively reported in malignancies including gliomas [17,18], ovarian [19], colorectal [20], gastric cancer [21], nasopharyngeal carcinomas [22], breast cancer [23] and chronic myeloid leukemia (CML) [24]. In gliomas, increased hBCATc and hBCATm expression has been limited to gliomas with wild-type isocitrate dehydrogenase 1 (IDH1), cytosolic and IDH2, mitochondrial [17,18].…”
Section: Introductionmentioning
confidence: 99%